1972
DOI: 10.1007/bf00165288
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for electron excitation of type III radio burst emission

Abstract: Type III radio bursts observed at kilometric wavelengths (~< 0.35 MHz) by the OGO-5 spacecraft are compared with > 45 keV solar electron events observed near I AU by the IMP-5 and Explorer 35 spacecraft for the period March 1968-November 1969 Fifty-six distinct type lI[ bursts extending to ~< 0.35 MHz (> 50 R| equivalent height above the photosphere) were observed above the threshold of the OGO-5 detector; all but two were associated with solar flares. Twenty-six of the bursts were followed ~< 40 min later by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Apparently, there is a variety of processes to produce these electrons: 1) The energy spectra extend smoothly to the suprathermal range, down to 2 keV, indicating that these events originate high in the corona (Potter et al, 1980). 2) Electrons accelerated at flare sites with a very wide energy spectrum that cause the radio type III bursts as discussed above (Alvarez et al, 1972). 3) Electrons accelerated at the propagating interplanetary shock waves, both upward and downward, leading to the characteristic "herringbone" pattern of radio spectra shown in Figure 19 .…”
Section: Seps: Electronsmentioning
confidence: 99%
“…Apparently, there is a variety of processes to produce these electrons: 1) The energy spectra extend smoothly to the suprathermal range, down to 2 keV, indicating that these events originate high in the corona (Potter et al, 1980). 2) Electrons accelerated at flare sites with a very wide energy spectrum that cause the radio type III bursts as discussed above (Alvarez et al, 1972). 3) Electrons accelerated at the propagating interplanetary shock waves, both upward and downward, leading to the characteristic "herringbone" pattern of radio spectra shown in Figure 19 .…”
Section: Seps: Electronsmentioning
confidence: 99%
“…The observations of the type III radiation using the satellite have been made the start with the ATS-II satellite for the frequency range of 3.0 MHz to 450 kHz (ALEXANDER et al, 1969), then observation study of long wave type HI radio burst has been expanded by using OGO-III (GRAEDEL, 1970), and by Radio Astronomy Explorer (RAE-1) satellite (MOHR et al, 1969;EVANS et al, 1971), OGO-5 and IMP-6 (FRANK and GURNETT, 1972;EvANS et al, 1973;ALVAREZ et al, 1972 andKAISER, 1975). Discussions have been raised for the generation mechanism of type III radio bursts; whether the source is fundamental frequency of the Langmuir waves or the second harmonics of the generated waves, which are formed as the results of the nonlinear coupling processes.…”
Section: Plasma Waves Observed By the Exos-d Satellitementioning
confidence: 99%
“…Evenson et al (1984) found that electrons with energies from 5 to 50 MeV in SEP events are always associated with solar flares. Type III radio bursts are also induced by beams of energetic electrons escaping intointerplanetary space from flare sites (e.g., Alvarez et al 1972;Chen & Petrosian 2012). In this study, we investigate acceleration of electrons in a current sheet with cascading reconnection, which may explain hard X-ray (HXR) emissions at flare sites and energetic electrons in SEP events.…”
Section: Introductionmentioning
confidence: 99%